2008
DOI: 10.1007/s00383-008-2184-y
|View full text |Cite
|
Sign up to set email alerts
|

Does leflunomide attenuate the sepsis-induced acute lung injury?

Abstract: The organ that is affected first and most severely in intraabdominal sepsis is the lung. Oxygen radicals and active neutrophils in the lung are important sources for severe pulmonary inflammation leading to acute lung injury (ALI)/acute respiratory distress syndrome. The aim of this study was to investigate the effects of leflunomide, an immunomodulatory agent, on oxidant/antioxidant status with nitric oxide (NO) level and myeloperoxidase (MPO) activity in rats with sepsis-induced ALI. Fifty male Wistar albino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In other models of lung injury, it has been shown that treatment with immunoregulatory drugs decreases the production of ROS and MPO [36,37]. We hypothesize that the same effect would occur in PbA-induced ALI/ARDS, predicting that without ROS and MPO, NET formation would not occur; however, this remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 76%
“…In other models of lung injury, it has been shown that treatment with immunoregulatory drugs decreases the production of ROS and MPO [36,37]. We hypothesize that the same effect would occur in PbA-induced ALI/ARDS, predicting that without ROS and MPO, NET formation would not occur; however, this remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 76%
“…The leflunomide treatment also reversed this high SOD activity. Ozturk et al [34] demonstrated that leflunomide treatment against a sepsis model in rats reversed the MDA level and MPO activities in lung tissue. They found that sepsis caused the decrease in antioxidant enzyme activities, including CAT, GSH-Px and SOD.…”
Section: Discussionmentioning
confidence: 98%
“…CAT and GSH-Px are two major endogen antioxidant enzymes that detoxify hydrogen peroxide to water. However, SOD catalyzes the specific reaction that yields hydrogen peroxide, one of the major ROS [34]. Overexpression of SOD results in increased dismutation of superoxide anion to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic elevations in the levels of proinflammatory cytokines such as tumor necrosis factor (TNF-α) and several interleukins (i.e., IL-1, IL-6 and IL-10) play a chief role within this phenomenon 4. The lung is the organ which is affected initially, and sepsis leads to severe injury in lung tissue 5. It has been shown that pericytes in lung tissue produce proinflammatory cytokines in response to lipopolysaccharide (LPS) 6.…”
Section: Introductionmentioning
confidence: 99%